A Smart Shopping Cart for Automated Billing and Personalized Recommendations - Pokhrel, Suman; Pradhan, Gagan; Khati, Manoj; Rai, Anamika; Luitel, Shiva Raj (International Journal on Engineering Technology, 2025)
This study presents a Smart Shopping Cart system integrating QR code technology with a Flutter-based mobile application to enhance the traditional retail experience in Nepal. The system employs QR codes for cart identification and product tracking, synchronized with a Firebase database in real time. A tablet-mounted application provides instant cart updates and personalized product recommendations using an item-based content filtering algorithm. By supporting online payments, it reduces checkout times and manual interventions. Testing over 50 cycles with 100 products and 20 users achieved an 85% recommendation accuracy and a 640.8 ms registration time, confirming efficiency. Tailored for Nepal’s retail challenges, this scalable solution bridges physical and digital shopping, improving customer convenience and operational performance.